Low proportion of women who came knowing their HIV status at first antenatal care visit, Uganda, 2012-2016: a descriptive analysis of surveillance data - Miriam Nakanwagi; Lilian Bulage; Benon Kwesiga; Alex Riolexus Ario; Doreen Agasha Birungi; Ivan Lukabwe; John Bosco Matovu; Geoffrey Taasi; Linda Nabitaka; Shaban Mugerwa; Joshua Musinguzi (BMC, 2020)
Abstract Background HIV testing is the cornerstone for HIV care and support services, including Prevention of Mother to Child Transmission of HIV (PMTCT). Knowledge of HIV status is associated with better reproductive health choices and outcomes for the infant's HIV status. We analyzed trends in known current HIV status among pregnant women attending the first antenatal care (ANC) visit in Uganda, 2012-2016. Methods We conducted secondary data analysis using District Health Information Software2 data on all pregnant women who came for ANC visit during 2012-2016. Women who brought documented HIV negative test result within the previous 4 weeks at the first ANC visit or an HIV positive test result and/or own HIV care card were considered as knowing their HIV status. We calculated proportions of women with known current HIV status at first ANC visit, and described linear trends both nationally and regionally. We tested statistical significance of the trend using modified Poisson regression with generalized linear models. For known HIV positive status, we only analyzed data for years 2015-2016 because this is when this data became available. Results There was no significant difference in the number of women that attended first ANC visits over years 2012-2016. The proportion of women that came with known HIV status increased from 4.4% in 2012 to 6.9% in 2016 and this increase was statistically significant (p < 0.001). Most regions had an increase in trend except the West Nile and Mid-Eastern (p < 0.001). The proportion of women that came knowing their HIV positive status at first ANC visit was slightly higher than that of women that were newly tested HIV positive at first ANC visit in 2015 and 2016. Conclusion Although the gap in women that come at first ANC visit without knowing their HIV positive status might be reducing, a large proportion of women who were infected with HIV did not know their status before the first ANC visit indicating a major public health gap. We recommend advocacy for early ANC attendance and hence timely HIV testing and innovations to promptly identify HIV positive women of reproductive age so that timely PMTCT interventions can be made.